Acceptance of rice farming technology by paddy growers in granary areas of integrated agricultural development project (IADP) Penang / Zainol Ahmad - Ahmad, Zainol (2005)
Even though the Ministry of Agriculture and the Malaysian Agricultural Research and Development Institute (MARDI) released super yielding paddy varieties suitable for double cropping such as MR 219 and MR 220 that could achieve 10 tons per hectare, paddy yield in the Penang rice bowl areas of Integrated Agricultural Development Project (IADP) is generally below 5.0 tons per hectare. The study was carried out to evaluate the possible reasons f or paddy growers obtaining such a low yield. The methodology of study comprised the formulation of questionnaire which was used for field survey and subsequently the analysis of data. It comprised the questionnaire covering both quantitative and qualitative approaches. The data collected were subjected to statistical analysis using Statistical Analysis System (SAS), which included the analysis of variance and multivariate analysis. Several factors had contributed to low paddy yield. They included the lackadaisical attitude of the majority of the paddy growers in the cultivation of paddy. In addition, other contributing factors included high dependence of paddy growers on external service providers and unwillingness of the paddy growers to adopt the recommended technological package provided by MARDI. Paddy growers discriminated cultural practices almost at all levels of crop requirements.